Pemanfaatan FABA, Tawas dan Kapur Untuk Menetralkan Air Asam Tambang - Indra Siregar; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2021)
Coal is the most important source of energy for electricity generation and serves as a basic fuel for industries such as steel and cement production as well as fuel for power generation. However, it is undeniable that the continuous use of coal also produces negative impacts from the mining process, namely acid mine drainage and coal processing in power plants, namely Fly Ash and Bottom Ash (FABA). Coal mining produces waste products in the form of acid mine drainage. FABA and Acid Mining Water (AAT) are two of the many negative effects of mining, so there is a need for awareness of the issues of damage that threaten the surrounding environment. FABA is solid waste produced from the coal combustion process for power generation. This study will discuss the use of FABA, alum and lime to neutralize acid mine drainage. Acid mine water obtained from PLTU X has a pH of 3.74. Neutralization of acid mine drainage is done by mixing AAT with FABA, AAT with alum and AAT with lime. Then proceed with mixing AAT with FABA and alum, mixing AAT with FABA and lime and mixing AAT with alum and lime. After that, mixing AAT with FABA, alum and lime. The results of this study provide variations in the composition of FABA, alum and lime which are good for neutralizing acid mine drainage  Keywords: Neutraluzation, Acid Mine Water (AAT), FABA, Alum, Lime